2003
DOI: 10.1016/j.rse.2003.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of IKONOS and Landsat for malaria control in the Republic of Korea

Abstract: Malaria reemerged in the Republic of Korea (ROK) in 1993. While limited numbers of U.S. soldiers in high-risk areas use chloroquine/ primaquine chemoprophylaxis to prevent malaria, control of mosquito larvae through larviciding also can be used to reduce the risk of malaria transmission. In order to estimate the cost of larviciding, accurate estimates of the spatial extent of mosquito larval habitats are necessary. The purpose of this study was to determine whether an accurate estimate of the area covered by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Remote sensing data are often employed to develop statistical land-cover associations and create maps of malaria hazard; Machault et al (2011) provide a recent review. Land-cover classifications have been related to vector abundance using a range of data sources including LANDSAT TM (DiukWasser et al, 2004;Bøgh et al, 2007;Charoenpanyanet and Chen, 2008), SPOT (Thomas and Lindsay, 2000;Dambach et al, 2009), ASTER, Quickbird (Stoops et al, 2008), RADARSAT (Kaya et al, 2004) and IKONOS (Masuoka et al, 2003;Minakawa et al, 2005b;Mutuku et al, 2009).…”
Section: Establishing Breeding Habitats From Land-use or Land-covermentioning
confidence: 99%
“…Remote sensing data are often employed to develop statistical land-cover associations and create maps of malaria hazard; Machault et al (2011) provide a recent review. Land-cover classifications have been related to vector abundance using a range of data sources including LANDSAT TM (DiukWasser et al, 2004;Bøgh et al, 2007;Charoenpanyanet and Chen, 2008), SPOT (Thomas and Lindsay, 2000;Dambach et al, 2009), ASTER, Quickbird (Stoops et al, 2008), RADARSAT (Kaya et al, 2004) and IKONOS (Masuoka et al, 2003;Minakawa et al, 2005b;Mutuku et al, 2009).…”
Section: Establishing Breeding Habitats From Land-use or Land-covermentioning
confidence: 99%
“…In 2003, Masuoka et al compared the Landsat 7 Enhanced Thematic Mapper (ETM)+, with a spatial resolution of 30 m, to IKONOS imagery, which has a spatial resolution of 4 m, to determine their respective effectiveness in malaria control [10]. They found that both the Landsat 7 ETM+ and IKONOS imagery could be used to reasonably estimate habitat area, but only the IKONOS imagery could detect the presence of smaller ponds, which could be a significant source of water in which mosquitoes could breed.…”
Section: Introductionmentioning
confidence: 99%
“…sinseni around two military camps. In this case, some pools were better detected with high-resolution Ikonos images (1 m resolution), even if no SWIR band was available (Masuoka et al, 2003). An example from the Kenyan highlands, which represents a very heterogenic ecosystem, is of interest in this connection, since the photo-interpretation of Ikonos images allowed the detection of 41% of the water collections, whereas the Landsat images (30 m resolution) did not provide any useful information (Mushinzimana et al, 2006).…”
Section: Breeding Sitesmentioning
confidence: 95%